2017
DOI: 10.1080/17482798.2017.1304970
|View full text |Cite
|
Sign up to set email alerts
|

Gender roles on social networking sites: investigating reciprocal relationships between Dutch adolescents’ hypermasculinity and hyperfemininity and sexy online self-presentations

Abstract: Gender roles on social networking sites: Investigating reciprocal relationships between Dutch adolescents' hypermasculinity and hyperfemininity and sexy online self-presentations van Oosten, J.M.F.; Vandenbosch, L.P.; Peter, J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 75 publications
2
36
0
2
Order By: Relevance
“…This finding is a significant contribution to the objectification theory research literature: though research has shown that young women primed with selfobjectification are more likely to behave in object-like ways in the presence of others (e.g., Saguy et al, 2010), scant research has considered how young women with high levels of trait self-objectification present themselves visually to others. This finding is also consistent with existing research that has similarly linked factors associated with self-objectification (i.e., engagement with sexually objectifying media and endorsement of gender stereotypes) with sexually objectified self-presentations (van Oosten et al, 2017;Vandenbosch et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is a significant contribution to the objectification theory research literature: though research has shown that young women primed with selfobjectification are more likely to behave in object-like ways in the presence of others (e.g., Saguy et al, 2010), scant research has considered how young women with high levels of trait self-objectification present themselves visually to others. This finding is also consistent with existing research that has similarly linked factors associated with self-objectification (i.e., engagement with sexually objectifying media and endorsement of gender stereotypes) with sexually objectified self-presentations (van Oosten et al, 2017;Vandenbosch et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Research has also found that the endorsement of gender stereotypes predicts male and female adolescents' sexy self-presentations and exposure to sexy self-presentations of others (van Oosten, Vandenbosch, & Peter, 2017). While these studies demonstrate links between selfobjectification-related factors and sexualised online self-presentations, little research has shown how young women who habitually self-objectify present themselves visually to others.…”
Section: Self-objectification Self-presentations and Audience Reactmentioning
confidence: 99%
“…In relation to reproducing dominant gender identities, Herring (2011, 2015), Ringrose (2011), andvan Oosten, Vandenbosch &Peter (2017) all found that young people use social media to replicate heightened versions of masculinity and femininity.…”
Section: Introductionmentioning
confidence: 99%
“…There is a constant debate regarding the existence and magnitude of gender differences. Studies have confirmed that gender stereotypes and stereotypical representations of males and females are frequently found on social networking sites ( Bailey et al., 2013 ; Glenn, 2013 ; van Oosten et al., 2017 ). Previous research showed gender differences in topics chosen for discussion ( Wang et al., 2013 ), in motivation for using social networks ( Barker, 2009 ; Haferkamp et al., 2012 ), in self-presentation ( Caldeira et al., 2018 ; Obertst et al., 2016a ).…”
Section: Introductionmentioning
confidence: 91%